Epilohmannia (Epilohmannia) cylindrica - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Epilohmannia (Epilohmannia) cylindrica (Berlese, 1904) Material – One specimen in Saraycık forest processing area, Taşköprü forest, N 41° 20′ 46.25′′, E 34° 33′ 15.72′′, alt. = 1223 m, 20 June 2018, dead P. nigra. Previous records in Turkey – Erzurum, Konya (Dik et al. 1999), Kayseri (Toluk and Ayyildiz 2008a), Kocaeli (Yaça and Baran 2019), Sakarya (Baran et al. 2015). Global distribution – Cosmopolitan. Ecology – Dry soils.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 257, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Epilohmannia cylindrica; Animalia; Epilohmannia; Biodiversity; Sarcoptiformes; Taxonomy; Epilohmanniidae; 2. Zero hunger; 15. Life on land